Exploring the Economic, Social, and Moral Justice Ramifications of the Warhol Decision - Menell, Peter S.; Mtima, Lateef (The Columbia Journal of Law & the Arts, 2024)
Beyond rectifying the interplay of the derivative work right and fair use, Justice Sotomayor’s vigorous, direct, and, at times, combative parrying with the dissent in Andy Warhol Foundation for the Visual Arts, Inc. v. Goldsmith drove a dagger into the free culture movement’s critique of copyright law. The resulting decision repudiates the movement’s campaign to undermine the derivative work right through a simplistic transformativeness shortcut for applying the fair use doctrine. As this Article explains, the Copyright Act’s drafters enhanced the financial rewards to, economic power of, and control of copyrighted works by authors through the grant of a bundle of exclusive rights, including a broad exclusive right to prepare derivative works. The Act tempered those rights through limiting doctrines, express recognition and codification of the fair use doctrine, and a series of statutory limitations, exemptions, and compulsory licenses. The codification of fair use, however, was not intended to “change, narrow, or enlarge” the doctrine outside of its traditional bounds—criticism, commentary, news reporting, educational, and research uses—“in any way.” The legislative history further noted courts’ freedom “to adapt the doctrine to particular situations on a case-by-case basis,” “especially during a period of rapid technological change.” Congress saw licensing as a principal vehicle for supporting cumulative creativity and ensuring fair compensation to and control of derivative uses by authors. Notwithstanding this foundation and the Supreme Court’s faithful interpretation of the fair use doctrine in Campbell v. Acuff-Rose Music, Inc., the fair use doctrine veered off course as lower courts collapsed Campbell’s nuanced framework into a simplistic transformativeness analysis. The collision of this approach with the derivative work right prompted the Supreme Court’s intervention. The resulting Warhol decision reinforced the economic and social empowerment undergirding the 1976 Act. After tracing the emergence of the free culture movement and the devolution of the fair use doctrine, this Article explores the economic, social justice, and moral right dimensions of the copyright regime reflected in the Warhol decision.